Manual 2009 de los Reglamentos del Empleo que Regulan a los Empleadores y Trabajadores Agrícolas de Florida: Derechos Civiles y Antidiscriminación - Fritz Roka; Michael Olexa; Katherine Smallwood; Leo Polopolus; Carol Fountain (EDIS)
This is part of a handbook by Fritz Roka, Michael Olexa, Katherine Smallwood, Leo Polopolus, and Carol Fountain. It is the Spanish language version of the 2009 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers. Published by the UF Department of Food and Resource Economics, October 2010.